2010
DOI: 10.1097/scs.0b013e3181d08c90
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cheek and Lower Eyelid Lymphedema After Resection of Oropharyngeal Tumor and Radiation

Abstract: Facial lymphedema, a rare condition with poorly understood pathogenesis, is commonly associated with previous infection, radiation therapy, local tumor growth, or previous surgery in the head and neck region. Few cases of isolated facial lymphedema have been reported in the literature. Surgical excision has emerged as the mainstay of therapy in such cases, although the long-term efficacy and recurrence rate after excision remain unknown. We present a unique case of a patient with severe unilateral facial lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[83] Lymphedema therapy consists of sequential manual lymphatic drainage of the edematous region according to Vodder's technique. [8485] This can be combined with compression garments.…”
Section: Rehabilitationmentioning
confidence: 99%
“…[83] Lymphedema therapy consists of sequential manual lymphatic drainage of the edematous region according to Vodder's technique. [8485] This can be combined with compression garments.…”
Section: Rehabilitationmentioning
confidence: 99%
“…Patients clinically present with painless, symmetrical non‐pitting edema localized to the forehead, infraorbital region, midface, nasal saddle, and nasolabial folds. The underlying pathogenesis of the disorder is continually debated in the literature but purportedly involves inflammatory injury to the cutaneous lymphatics (Wilkin,1994; Jansen et al,1998; Wohlrab etal.,2005; Nagasaka et al,2008). Ultimately, this manifests as persistent solid edema of the face, especially if the underlying disease entity is not recognized and treated in its early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary head and neck lymphedemas harbor a broad array of etiologies. Xanthomas and other infiltrative processes involving the dermis and subcutaneous tissues have been reported to be associated with development of secondary head and neck lymphedema (Tatnall and Sarkany,1988). B‐cell lymphomas (Dragan et al,2000), adenocarcinoma (Jang et al,1998) and lymphedema as part of paraneoplastic syndromes (Gudi et al,2009) have all been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these modalities are difficult to execute for many patients and are associated with poor long-term adherence given their time-consuming and costly nature 17 . For many patients, more extensive surgical therapy becomes the only management option 1820 . The current management of HNL is not standardized across institutions and has not been studied with long-term patient-reported outcomes.…”
Section: Introductionmentioning
confidence: 99%